Improvement of keli (Clarias sp.) genetic traits through selective breeding and hybridization - Mohd Daud, Hassan; Mohamad, Nora Faten Afifah; Christianus, Annie; A. R., Nordin; Saad, Che Roos; A. R., Abdullah; Y., Maheran; O., Rashidi; Hamid, Nur Hidayahanum; A. R., Mohd Khairuddin (Knowledge Transfer Programme – Ministry of Higher Education, Malaysia, 2015)
Currently, shortfalls in local supplies of high quality catfish seeds become one of the major problems for farmers that involved in Clarias catfish industries. However, since farmers realized the advantegous of hybrid Clarias catfish, interest in culturing of the hybrids as commercial food fish began to spin off and has been monopolized the catfish industries since then. Hybrid Clarias catfish has been quite popular among local farmers due to their overall improvement in performance such as better meat quality, good growth rates and survival rates, lower food conversion rates, high disease resistance and several others excellent characteristic of both species. To initiate the knowledge transfer, researchers and staff of Universiti Putra Malaysia had conducted short courses on artificial spawning techniques to several hatchery operators lead by an industrial partner, Andera Holdings Sdn. Bhd. in order to produce mass production of hybrid catfish as well as enhance the profitability of the farmer. A field trial was then conducted at Andera Holdings Sdn. Bhd’s small-scale hatchery located in Kg. Bendang Kering, Kuala Kangsar, Perak to evaluate the potentials of the hybrid of Keli Afrika, Clarias gariepinus (CG) (♂) x Keli Bunga, C.macrocephalus (CM) (♀) and C.gariepinus (CG) (♂) x Keli Kayu, C.batrachus (CB) (♀) in terms of survival and growth rates through artificial selective cross-breeding method. Several spawning sessions were successfully conducted in the Universiti Putra Malaysia hatchery and at the industrial partner’s farm. Unfortunately, the design of the hatchery of the industrial partner was not suitable and could not support the raising of the hatched fish larvae. The hatchery was open and not walled thus the fish larvae died at the early stage due to unsuitable water temperature and low dissolved oxygen. The industrial partner was asked to modify the hatchery lay-out accordingly.